2009
DOI: 10.1021/jf901983g
|View full text |Cite
|
Sign up to set email alerts
|

A Citrus Extract Containing Flavanones Represses Plasminogen Activator Inhibitor-1 (PAI-1) Expression and Regulates Multiple Inflammatory, Tissue Repair, and Fibrosis Genes in Human Colon Fibroblasts

Abstract: The consumption of flavonoid-rich Citrus extracts has been associated with multiple beneficial effects including anti-inflammatory properties, but the potential effects on the inflammatory responses in the gut have not been thoroughly investigated. We used microarrays to search for molecular changes induced in human colon fibroblasts in response to the exposure to a flavanone-rich bitter orange extract under physiologically representative conditions. Dietary nontoxic levels of the predigested extract induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…The extract was composed of approximately 42.1% soluble flavanones (% of the powder extract) with one most abundant compound, naringin (24.5 ± 2.6%), followed by neohesperidin (11.4 ± 0.8%), hesperidin (1.7 ± 0.4%), naringenin (0.4 ± 0.1%), hesperetin (0.4 ± 0.1%), and isosakuranetin (0.2 ± 0.1%). 5 The structures of the three main flavanone constituents of the orange extract are shown in Figure 1. The extract (a hygroscopic brown powder, 2.1% humidity) was kept in a tightly closed container within a desiccator at room temperature, and fresh stock solutions were prepared by dissolving 0.1 g of the powder extract in 50 mL of water.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extract was composed of approximately 42.1% soluble flavanones (% of the powder extract) with one most abundant compound, naringin (24.5 ± 2.6%), followed by neohesperidin (11.4 ± 0.8%), hesperidin (1.7 ± 0.4%), naringenin (0.4 ± 0.1%), hesperetin (0.4 ± 0.1%), and isosakuranetin (0.2 ± 0.1%). 5 The structures of the three main flavanone constituents of the orange extract are shown in Figure 1. The extract (a hygroscopic brown powder, 2.1% humidity) was kept in a tightly closed container within a desiccator at room temperature, and fresh stock solutions were prepared by dissolving 0.1 g of the powder extract in 50 mL of water.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…3 Therefore, these flavanone glycosides can reach the colon in their intact molecular form and may exert some effects on the microorganisms present in the distal part of the intestine. 4,5 Recently, several studies have demonstrated that certain flavonoids can act as inhibitors of the virulence of pathogenic bacteria by interfering with quorum sensing (QS) mechanisms. 6,7 QS is a regulatory mechanism that enables bacteria to make collective decisions with respect to the expression of a specific set of genes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This indicated that orally administered CK or KM can decrease thrombotic tendencies induced by inflammation in mice. We found that PAI-1 production was significantly suppressed in the plasma of mice after consuming CK and KM for four weeks, a time-frame that is appropriate to explore anti-thrombotic effects in mice [11] [25] [26].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al reported that green tea polyphenols inhibit PAI-1 expression and secretion in endothelial cells [10]. A citrus extract containing flavones represses PAI-1 expression in human colon fibroblasts [11].…”
Section: Introductionmentioning
confidence: 99%
“…For comparative purposes, the effect of both PFASs in presence or absence of IL-1b, an essential pro-inflammatory cytokine in mediating the inflammatory response (Powell et al, 2011) was investigated. Furthermore, since fetal bovine serum (FBS) can influence mechanisms associated to inflammation in these cells (Giménez-Bastida et al, 2009;González-Sarrías et al, 2010), and proteins of FBS such as albumin can interact with PFOS and PFOA (Chen and Guo, 2009) different concentrations of serum were used in this study. Therefore, the aim of this study was to perform an evaluation of the ability of PFOS and PFOA to induce cytotoxicity and modulate mechanisms associated with inflammation, including (i) colon fibroblasts viability, (ii) colon fibroblasts proliferation, and (iii) IL-6 production.…”
Section: Introductionmentioning
confidence: 99%